Telegram from Marianne Homburger to Max Bredig, April 1941 - Homburger, Marianne (1941)
Marianne Homburger (1903-1986) sends her brother, Max Bredig (1902-1977) a check number for a money transfer.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Jewish Holocaust (1939-1945)